Quantum-chemical calculation of fragments of silica functionalized by nitrogen-, phosphorus- and sulfur-containing groups - Мирошниченко, Юлия Анатольевна; Безносик, Юрий Александрович; Смирнова, Олеся Валентиновна; Зуб, Юрий Леонидович (Eastern-European Journal of Enterprise Technologies, 2012)
As a result of quantum-chemical calculations (DFT/b3lyp/6-31g(d,p) of fragments, which reflect the surface structure of xerogels, functionalized by amine, phosphinoxide and thiourea groups, the geometrical parameters of these complexing group and the potential existence of they intramolecular interactions were found